Advanced oxidative processes in the treatment of textile effluents applicable to the local production arrangement of clothing factories in the Agreste Pernambucano (Research, Society and Development, 2024)
The growth of cities in recent decades is responsible for increased human pressure on natural resources, especially water bodies. The environmental impacts caused by the discharge of effluents are not always detected in advance. Considering this problem, this work aims to investigate and analyze the POAs, and the feasibility of applying these processes in the Local Production Arrangement of Clothing in Agreste Pernambucano and in industries in general. To carry out the research, a bibliographic review was carried out on POAs based on the PRISMA systematic analysis methodology, together with the VosViewer software. The investigation was carried out due to the importance of APLCAPE and the need to apply new methods for treating textile effluents. Through analysis and review of articles in the Scopus and Web of Science databases, it was found that processes based on the Fenton reagent were studied in the reference period, with emphasis on the application of photocatalysis. The research also found that the most evident citations in scientific articles relating to POAs are the words textile industry, wastewater treatment and oxidation. These treatment processes are possible to be implemented in APLCAPE, the use of POAs can be an effective alternative for reducing the environmental impacts generated by textile effluents. By using these treatment techniques, it is possible to promote environmental sustainability linked to sustainable development. Even so, there are still gaps regarding these effluent treatment techniques.